Potensi dan Peranan Zakat dalam Pengentasan Kemiskinan di Kota Gorontalo - Syawaluddin S (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2023)
This research aims to examine and analyze the potential and role of zakat in alleviating poverty in Gorontalo City. This research is descriptive research with data collection methods such as observation, interview, and literature study. Data were analyzed qualitatively through data collection, data reduction, and data presentation. Data were validated through source triangulation and method triangulation. The results showed that the potential of zakat in Gorontalo City is quite large obtained by the National Amil Zakat Agency of Gorontalo City, which in 2021 reached 4.0 billion, but has not been maximally explored due to several obstacles, both institutionally and personally for zakat recipients (mustahik). The contribution of zakat to the Gross Regional Domestic Product of Gorontalo City from 2019 until now continues to increase, reaching an average of 10.55%. This shows that zakat can contribute well to help government programs in poverty alleviation. The role of zakat towards poverty alleviation efforts in Gorontalo City runs in several forms of assistance schemes, including the humanitarian field and the productive economic field. The implementation of zakat management by the National Amil Zakat Agency of Gorontalo City is evaluated and improved so that the achievement of the existing zakat potential can be maximally explored to achieve the maximum role in poverty alleviation.